Rough endoplasmic reticulum expansion: a consistent finding in a patient cohort with vascular Ehlers-Danlos Syndrome and Osteogenesis Imperfecta. (2nd November 2021) - Redman, Melody G; Wagner, Bart E; Cadden, Sophie; Baker, Duncan; Bowen, Jessica M; Johnson, Diana; Sobey, Glenda; Balasubramanian, Meena
ABSTRACT: Vascular Ehlers-Danlos Syndrome (vEDS) and Osteogenesis Imperfecta (OI) are two forms of connective tissue disorders. Previously, transmission electron microscopy of skin biopsies was routinely performed on all patients who were clinically suspected to have vEDS. At present, molecular genetics using genomic DNA extracted from a blood sample is the first line investigation for these patients. However, when variants of uncertain clinical significance are identified on genetic testing and individuals do not have the classical features of OI or vEDS, additional phenotypic information obtained from a skin biopsy can be valuable for contributing to the evidence for re-classifying pathogenicity of variants. We present a cohort of six patients with molecularly confirmed vEDS and one patient with a severe form of OI, who each had expanded (or dilated), protein-filled, rough endoplasmic reticulum identified on transmission electron microscopy. The patients were identified through retrospective screening of medical records, and biopsies were taken between 1999–2016. We discuss the potential role for assessing rough endoplasmic reticulum expansion as a useful tool to allow further phenotyping of these individuals.